Infusing Context Into Emotion Perception Impacts Emotion Decoding Accuracy - Hess, Ursula; Kafetsios, Konstantinos (Experimental psychology, 2021)
The accurate decoding of facial emotion expressions lies at the center of many research traditions in psychology. Much of this research, while paying lip service to the importance of context in emotion perception, has used stimuli that were carefully created to be deprived of contextual information. The participants' task is to associate the expression shown in the face with a correct label, essentially changing a social perception task into a cognitive task. In fact, in many cases, the task can be carried out correctly without engaging emotion recognition at all. The present article argues that infusing context in emotion perception does not only add an additional source of information but changes the way that participants approach the task by rendering it a social perception task rather than a cognitive task. Importantly, distinguishing between accuracy (perceiving the intended emotions) and bias (perceiving additional emotions to those intended) leads to a more nuanced understanding of social emotion perception. Results from several studies that use the Assessment of Contextual Emotions demonstrate the significance and social functionality of simultaneously considering emotion decoding accuracy and bias for social interaction in different cultures, their key personality and societal correlates, and their function for close relationships processes.
Keywords: emoce; Bias; Facial Expression; Social Perception; Emotions; emotion perception; social perception; zkreslení výsledků (epidemiologie); Humans; accuracy; bias; Personality; sociální percepce; osobnost; výraz obličeje; lidé